Islamic Business Ethics and National Economic Sustainability: A Macroeconomic Analysis of the Indonesian Landscape - Abdurrahman; Safa Salsabila Kurnia Widayanti; Fika Nurdiana; Maysara; Achmad Basofitrah (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the role of Islamic Business Ethics in supporting National Economic Sustainability within the Indonesian macroeconomic landscape. The study is grounded in the view that economic sustainability cannot be understood solely through growth indicators, but must also be linked to the ethical quality of economic behavior, governance, and institutional practice. Using a quantitative approach with an explanatory design, this research involved 180 respondents selected through purposive sampling. Data were collected through a structured questionnaire and analyzed using SPSS through descriptive statistics, validity and reliability tests, classical assumption tests, and linear regression analysis. The findings reveal that Islamic Business Ethics has a positive and significant effect on National Economic Sustainability in Indonesia. Ethical principles such as honesty, justice, trustworthiness, transparency, and social responsibility were found to contribute meaningfully to perceptions of economic stability, resilience, inclusiveness, and long-term sustainability. The coefficient of determination indicates that Islamic Business Ethics explains a substantial portion of the variance in National Economic Sustainability, although other factors also contribute to the model. Theoretically, this study extends the literature by positioning Islamic Business Ethics as a macro-level analytical variable rather than merely a micro-level or normative construct. Practically, the findings suggest that sustainable national development strategies should integrate ethical reinforcement in public policy, governance, business conduct, and economic education. This study highlights that the long-term sustainability of Indonesia’s economy depends not only on structural and technical reforms, but also on the ethical foundations that shape economic behavior and institutional trust.